Evolution and ontogeny of bacteriocytes in insects - Alarcón, Mauricio E.; Polo, Priscila G.; Akyüz, Sevim Nur; Rafiqi, Ab. Matteen (Frontiers in Physiology, 2022)
The ontogenetic origins of the bacteriocytes, which are cells that harbour bacterial intracellular endosymbionts in multicellular animals, are unknown. During embryonic development, a series of morphological and transcriptional changes determine the fate of distinct cell types. The ontogeny of bacteriocytes is intimately linked with the evolutionary transition of endosymbionts from an extracellular to an intracellular environment, which in turn is linked to the diet of the host insect. Here we review the evolution and development of bacteriocytes in insects. We first classify the endosymbiotic occupants of bacteriocytes, highlighting the complex challenges they pose to the host. Then, we recall the historical account of the discovery of bacteriocytes. We then summarize the molecular interactions between the endosymbiont and the host. In addition, we illustrate the genetic contexts in which the bacteriocytes develop, with examples of the genetic changes in the hosts and endosymbionts, during specific endosymbiotic associations. We finally address the evolutionary origin as well as the putative ontogenetic or developmental source of bacteriocytes in insects.